A pre‐specified statistical analysis plan for the VERIFY study: Vildagliptin efficacy in combination with metformin for early treatment of T2DM. Issue 10 (30th June 2019) - Matthews, David R.; Paldánius, Päivi M.; Stumvoll, Michael; Han, Jackie; Bader, Giovanni; Chiang, YannTong; Proot, Pieter; Del Prato, Stefano
Abstract: Aims: To ensure the integrity of the planned analyses and maximize the clinical utility of the VERIFY study results by describing the detailed concepts behind its statistical analysis plan (SAP) before completion of data collection and study database lock. The SAP will be adhered to for the final primary data analysis of the VERIFY trial. Materials and Methods: Vildagliptin efficacy in combination with metformin for early treatment of T2DM (VERIFY) is an ongoing, multicentre, randomized controlled trial aiming to demonstrate the clinical benefits of glycaemic durability and glucose control achieved with an early combination therapy in newly‐diagnosed type 2 diabetes (T2DM) patients. Results: The SAP was initially designed at the study protocol conception phase and later modified, as reported here, in collaboration between the steering committee members, statisticians, and the VERIFY study leadership team. All authors were blinded to treatment allocation. An independent statistician has additionally retrieved and presented unblinded data to the independent data safety monitoring committee. An overview of the trial design with a focus on describing the fine‐tuning of the analysis plan for the primary efficacy endpoint, risk of initial treatment failure, and secondary, exploratory and pre‐specified subgroup analyses is provided here. Conclusion: According to optimal trial practice, the details of the statistical analysis and data‐handling plan prior to locking the database are reported here. The SAP accords with high‐quality standards of internal validity to minimize analysis bias and will enhance the utility of the reported results for improved outcomes in the management of T2DM.